Providing a Framework for Factors Affecting the Promotion of Social Responsibility in Free Zones with the Foundation Data Method - alireza bahador; Soheila Zarinjoy Alvar; leila andervazh (توسعه اجتماعی, 2024)
Social responsibility provides solutions where organizations can meet the commercial, legal and ethical needs of society, because every economic enterprise has several responsibilities in social, economic and legal fields that it is obliged to comply with. They are towards their employees, shareholders, government and partners. The main purpose of this article is to provide a framework for the factors affecting the promotion of social responsibility in free zones with the foundation data method. The studied population is experts from the Arvand Azad region. 15 people were selected by snowball sampling. The results of the research include 12 main categories under the title of causal factors, intervening factors, contextual factors, strategies, central phenomenon and research outcomes, including information, structural link, power, orientation, knowledge, moral responsibility, legal responsibility, economic responsibility, social responsibility structural weakness, the destructive role of some managers and the inefficient monitoring system, which was presented in the form of the paradigm model of the foundation's data theory.